NLRP3 Inflammasome-Mediated Pyroptosis Pathway Contributes to the Pathogenesis of Candida albicans Keratitis - Lian, Huifang; Fang, XiaoLong; Li, Qingyu; Liu, Shuang; Wei, Qiuhong; Hua, Xia; Li, Wenguang; Liao, Chunyang; Yuan, Xiaoyong (Frontiers in Medicine, 2022)
Purpose: Fungal keratitis is a sight-threatening corneal infection caused by fungal pathogens, and the pathogenic mechanisms have not been fully elucidated. The aim of this study was to determine whether NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome-mediated pyroptosis contributes to Candida albicans (C. albicans) keratitis and explore the underlying mechanism. Methods: An in vivo mouse model of C. albicans keratitis and an in vitro culture model of human corneal epithelial cells (HCECs) challenged with heat-killed C. albicans (HKCA) were established in this study. The degree of corneal infection was evaluated by clinical scoring. Gene expression was assessed using genetic microarray analysis or quantitative real-time PCR (qRT–PCR), and western blot analysis or immunofluorescence staining was performed to evaluate protein expression. A lactate dehydrogenase (LDH) release assay was performed to assess cytotoxicity. Results: Microarray analysis showed that the transcript levels of NLRP3, caspase-1 (CASP1), interleukin (IL) -1β and gasdermin-D (GSDMD) were significantly upregulated in C. albicans keratitis compared to those in mock-infected corneas, and the results were further verified by qRT–PCR. Our data also demonstrated that the protein expression of NLRP3 and the pyroptosis-related markers apoptosis-associated speck-like protein containing a CARD (ASC), cleaved CASP1, N-GSDMD, cleaved IL-1β and IL-18 were dramatically elevated in the mouse model of C. albicans keratitis. More importantly, NLRP3 knockdown markedly alleviated pyroptosis and consequently reduced corneal inflammatory reaction in C. albicans keratitis. In vitro, the presence of activated NLRP3 inflammasome and pyroptotic cell death were validated in HCECs exposed to HKCA. Furthermore, the potassium (K+) channel inhibitor glyburide suppressed NLRP3 inflammasome activation and pyroptosis in HCECs exposed to HKCA. Conclusion: In conclusion, the current study revealed for the first time that pyroptosis in corneal epithelial cells triggered by NLRP3 inflammasome activation contributes to the progression of corneal inflammation and the pathogenesis of C. albicans keratitis. This NLRP3 inflammasome-mediated pyroptosis pathway may be an attractive target for the treatment of fungal keratitis.